Differences in healthcare visit frequency and type one year prior to stroke among young versus middle-aged adults - Brandi L. Vollmer; Xing Chen; Erin R. Kulick; Mitchell S. V. Elkind; Amelia K. Boehme (BMC, 2021)
Abstract Background The incidence and prevalence of stroke among the young are increasing in the US. Data on healthcare utilization prior to stroke is limited. We hypothesized those < 45 years were less likely than those 45-65 years old to utilize healthcare in the 1 year prior to stroke. Methods Patients 18-65 years old who had a stroke between 2008 and 2013 in MarketScan Commercial Claims and Encounters Databases were included. We used descriptive statistics and logistic regression to examine healthcare utilization and risk factors between age groups 18-44 and 45-65 years. Healthcare utilization was categorized by visit type (no visits, inpatient visits only, emergency department visits only, outpatient patient visits only, or a combination of inpatient, outpatient or emergency department visits) during the year prior to stroke hospitalization. Results Of those 18-44 years old, 14.1% had no visits in the year prior to stroke compared to 11.2% of individuals aged 45-65 [OR = 1.30 (95% CI 1.25,1.35)]. Patients 18-44 years old had higher odds of having preventive care procedures associated with an outpatient visit and lower odds of having cardiovascular procedures compared to patients aged 45-65 years. Of stroke patients aged 18-45 and 45-65 years, 16.8 and 13.2% respectively had no known risk for stroke. Conclusions Patients aged 45-65 were less commonly seeking preventive care and appeared to be seeking care to manage existing conditions more than patients aged 18-44 years. However, as greater than 10% of both age groups had no prior risk, further exploration of potential risk factors is needed.